2018
DOI: 10.1002/ajhb.23164
|View full text |Cite
|
Sign up to set email alerts
|

Association between FTO gene polymorphism and excess body weight in women from before to after pregnancy: A cohort study

Abstract: The FTO-rs9939609 polymorphism was associated with increased weight and BMI in mothers before and after pregnancy. However, we found no significant effect of the polymorphism on excess body weight of women during the reproductive trajectory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…An in-depth description of the PREDI Study has been published previously (28)(29)(30)(31) . Briefly, all women over 18 years of age who gave birth to a full-term singleton (between 37 and 42 weeks of gestation) admitted to a public maternity hospital in Joinville (Brazil) from 14 January to 16 February 2012 were invited to participate.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…An in-depth description of the PREDI Study has been published previously (28)(29)(30)(31) . Briefly, all women over 18 years of age who gave birth to a full-term singleton (between 37 and 42 weeks of gestation) admitted to a public maternity hospital in Joinville (Brazil) from 14 January to 16 February 2012 were invited to participate.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…The A allele for the rs9939609 polymorphism in the FTO gene was previously associated with higher BMI before and after pregnancy [ 38 , 39 ] but not with excessive GWG [ 15 ] in Brazilian women. Studies from the USA [ 12 , 13 ] and Spain [ 14 ] found a higher risk of having higher GWG among A-allele carriers, contradicting the results from Turkey [ 40 ] and Mexico [ 41 ], both without association.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on 406 Brazilian adult women, it was reported that there was a higher frequency of excessive GWG in those with the TT genotype (51%) compared to those with other genotypes; however, this finding did not have statistical significance, and Caucasian women did not report any associations. Only this genetic variant was associated with pBMI and the period after delivery [ 27 ] until 2–4 years postpartum. This phenomenon could begin to occur at young ages via the LEPR SNV, which could modify some metabolic indicators [ 50 ].…”
Section: Relevant Sectionsmentioning
confidence: 99%
“…The association between specific genetic variants and excessive GWG has been evaluated in 6974 women. The most recent studies came from the United States of America [17,[21][22][23][24], Brazil [25][26][27][28], Romania [29,30], Turkey [31,32], Ukraine [33,34], Canada [35], Germany [36], China [37], and Poland [38]. These studies were performed on pregnant adult women (aged [22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Relevant Sections 21 What Is the Role Of Genomic Sciences In...mentioning
confidence: 99%
See 1 more Smart Citation